Use of intrauterine dextrose as an alternative to systemic antibiotics for treatment of clinical metritis in dairy cattle: a microbiome perspective - Lection, Jennine; Van Syoc, Emily; Miles, Asha; Hamilton, Julia; Martinez, Marcela; Bas, Santiago; Silverman, Justin; Barragan, Adrian; Ganda, Erika (Frontiers in Veterinary Science, 2024)
IntroductionClinical metritis (CM) has significant costs to dairy producers. Current treatment strategy involves systemic antibiotics; however, there is increasing concern about judicious antibiotic use. The study objective was to evaluate the effects of a non-antibiotic treatment vs. systemic antibiotic therapy on the vaginal discharge microbiome of dairy cows diagnosed with CM at 7 ± 3 DIM (days in milk). We hypothesize that both treatment methods will have a similar impact on the reproductive microbiome due to broad-spectrum bactericidal activity; therefore, there will not be significant differences amongst the microbiota after the completion of therapy.MethodsCows from a central Pennsylvania dairy were screened for CM at 7 ± 3 days DIM using a Metricheck™ device (n = 351). Cows with red-brown watery discharge were diagnosed with CM and eligible for enrollment. Eligible cows (n = 77) were blocked by parity and randomly allocated to one of two treatments starting on the day of diagnosis: (1) Intrauterine dextrose (DEX, n = 38): 1 l of an intrauterine 50% dextrose solution for 3 days, and (2) Systemic ceftiofur (CONV, n = 39): two injections of ceftiofur (6.6 mg/Kg of BW; Excede, Zoetis Inc.) 72 h apart. Cows were evaluated for clinical cure rate at 7 ± 3 and 14 ± 3 days post-diagnosis. Vaginal discharge samples were collected using the Metricheck™ at enrollment day [study day (sd) 0, pre-treatment], sd 7, and sd 14 for a subset of enrolled cows (DEX = 13, CONV = 14). Vaginal discharge samples were analyzed with 16S rRNA sequencing to evaluate changes in the microbiome between treatments.ResultsAfter treatment, there were only minor differences within the microbiome between the two treatments indicating the potential suitability of dextrose as an antibiotic-alternative treatment. Alpha diversity did not differ (Welch's t-test) between the treatments at any of the time points. Beta diversity based on PERMANOVA analysis did differ between treatments at sd 0 (P = 0.014) and again at sd 14 (P = 0.028), but not at sd 7 (P = 0.261).DiscussionWhile 16S rRNA analysis does not provide information on bacterial viability, the relative similarity of the microbiome between the two groups immediately following treatment might suggest that intrauterine dextrose could be utilized as an alternative treatment for CM.